2016
DOI: 10.17221/430/2015-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial characteristics of orange pigment extracted from Monascus pigments against Escherichia coli

Abstract: Zhao G.P., Li Y.Q., Yang J., Cui K.Y. (2015): Antibacterial characteristics of orange pigment extracted from Monascus pigments against Escherichia coli. Czech J. Food Sci.,.The antibacterial characteristics of orange pigment, which is one of the Monascus pigments, against Escherichia coli were investigated. Orange pigment exhibited strong antibacterial activity against E. coli evidenced by an increase in the diameter of inhibition zone with orange pigment treatment. The concentration of 2.5 mg/ml was the minim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 34 publications
(29 reference statements)
0
7
1
Order By: Relevance
“…1 D and F , bacteria incubated with polymer film or polymer nanomesh had no cell wall disruption of the bacteria and no external ultrastructural changes with regular and typical morphology. Moreover, the cell sizes were uniform, as presented in the existing studies ( 39 ). In contrast, there were significant morphological changes in the cells exposed to copper nanomesh, as shown in Fig.…”
Section: Resultsmentioning
confidence: 62%
“…1 D and F , bacteria incubated with polymer film or polymer nanomesh had no cell wall disruption of the bacteria and no external ultrastructural changes with regular and typical morphology. Moreover, the cell sizes were uniform, as presented in the existing studies ( 39 ). In contrast, there were significant morphological changes in the cells exposed to copper nanomesh, as shown in Fig.…”
Section: Resultsmentioning
confidence: 62%
“…The suitability of Monascus pigments for coloring meat products, particularly with regard to color, texture, smell and other sensory parameters of the products, has already been proven in the scientific literature (Leistner et al, 1991;Fabre et al, 1993;Yu et al, 2015;Seong et al, 2017). In addition, inhibitory effects of Monascus pigments or Monascus extracts on vegetative bacterial cells, e.g., Staphylococcus aureus, Escherichia coli, Bacillus subtilis (Kim et al, 2006;Vendruscolo et al, 2014;Zhao et al, 2016) have been demonstrated. In addition, the safety of Monascus pigments for human consumption has been confirmed in several studies (Bianchi, 2005;Yu et al, 2008;Mohan Kumari et al, 2009).…”
Section: Introductionmentioning
confidence: 95%
“…To extract the orange pigments from the filter cakes, a solvent with a polarity suitable for dissolving the orange pigments was required. Of the organic solvents permitted for use in the food industry (methanol, ethanol, ethyl acetate, acetone, and n-hexane) [54], ethyl acetate has been used for the extraction of orange pigments in previous studies [55,56]. Orange pigments are highly soluble in ethyl acetate, an amphiphilic volatile organic solvent.…”
Section: Preparation Process For Orange Monascus Pigments and Synthesis Of Derivativesmentioning
confidence: 99%